2006
DOI: 10.1534/genetics.105.051508
|View full text |Cite
|
Sign up to set email alerts
|

Fold Recognition of the Human Immunodeficiency Virus Type 1 V3 Loop and Flexibility of Its Crown Structure During the Course of Adaptation to a Host

Abstract: The third hypervariable (V3) region of the HIV-1 gp120 protein is responsible for many aspects of viral infectivity. The tertiary structure of the V3 loop seems to influence the coreceptor usage of the virus, which is an important determinant of HIV pathogenesis. Hence, the information about preferred conformations of the V3-loop region and its flexibility could be a crucial tool for understanding the mechanisms of progression from an initial infection to AIDS. Taking into account the uncertainty of the loop s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Expecting that the fitness of an amino acid depends mostly on the local structure surrounding each of the amino acid residues, Simons et al (1999aSimons et al ( , 1999b categorized local environments and calculated amino acid frequencies in the proteins registered in PDB for each of the categories (see below for more detail). Watabe et al (2006) obtained evidence that implies that the structure of the crown region of the HIV V3 loop varies more in the patient where the viral population experienced larger sequence evolution. They traced the value of PðseqjstrÞ based on the information of the sequences and the structure of the templates in PDB.…”
Section: A Likelihood-based Index Of the Binding Ability Of Protein-pmentioning
confidence: 99%
See 1 more Smart Citation
“…Expecting that the fitness of an amino acid depends mostly on the local structure surrounding each of the amino acid residues, Simons et al (1999aSimons et al ( , 1999b categorized local environments and calculated amino acid frequencies in the proteins registered in PDB for each of the categories (see below for more detail). Watabe et al (2006) obtained evidence that implies that the structure of the crown region of the HIV V3 loop varies more in the patient where the viral population experienced larger sequence evolution. They traced the value of PðseqjstrÞ based on the information of the sequences and the structure of the templates in PDB.…”
Section: A Likelihood-based Index Of the Binding Ability Of Protein-pmentioning
confidence: 99%
“…Particularly in the arms race of the host-parasite system, binding affinity plays a crucial role. Watabe et al (2006) developed a likelihood-based index, named sequencestructure fitness (SSF), which quantifies the degree to which a sequence fits in the given structure. The SSF is calculated empirically based on amino acid preferences and pairwise interactions in the structural environment present in templates' structure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, Watabe et al . [19] suggested empirical potentials to assess the fit of sequence variants to loop candidates generated by Monte Carlo variation of NMR peptide structures. So far, structural studies have been based on peptide structures, as no completely resolved structure of gp120 was available.…”
Section: Introductionmentioning
confidence: 99%
“…As Lusso [18] points out, structural understanding of coreceptor specificity is limited at the moment. In recent work, Watabe et al [19] suggested empirical potentials to assess the fit of sequence variants to loop candidates generated by Monte Carlo variation of NMR peptide structures. So far, structural studies have been based on peptide structures, as no completely resolved structure of gp120 was available.…”
Section: Structural Basis Of Coreceptor Usagementioning
confidence: 99%